The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.7763/ijcea.2013.v4.267
|View full text |Cite
|
Sign up to set email alerts
|

Surface Graft Polymerization of Acrylamide onto Plasma Activated Nylon Microfiber Artificial Leather for Improving Dyeing Properties

Abstract: Abstract-To improve surface wettability and dye-ability of Nylon microfiber artificial leather, we apply oxygen plasma treatment and subsequently graft-polymerize acrylamide (AAm) on the surface. The surface properties of AAm-grafted Nylon microfiber artificial leather are characterized by FT-IR, SEM, ESCA and dyeing density (C.I.reactive Blue 4). The dyeing rate of AAm-grafted Nylon microfiber artificial leather, up-regulated with higher acrylamide grafting concentration, increases to 67.1 mg/cm 2 , and remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…As Figure 4 shows of (a) un-modified, (b) O 2 plasma treatment (100 W), and (c) O 2 plasma treatment (100 W) +UV graft thermo-sensitive AgNPs hydrogels BC specimens. It could be observed that several adsorption peaks after O 2 plasma treatment appeared, such as, for example, -OH at 3050~3250 cm −1 , C=O at 1700–1720 cm −1 , and C-O at 1140 cm −1 , were reduced [ 37 , 38 , 39 , 40 , 41 ]. The increase in these oxygen-containing functional groups revealed the due to oxygen atom bonding to hydrogen atoms on the surface during O 2 plasma treatment [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As Figure 4 shows of (a) un-modified, (b) O 2 plasma treatment (100 W), and (c) O 2 plasma treatment (100 W) +UV graft thermo-sensitive AgNPs hydrogels BC specimens. It could be observed that several adsorption peaks after O 2 plasma treatment appeared, such as, for example, -OH at 3050~3250 cm −1 , C=O at 1700–1720 cm −1 , and C-O at 1140 cm −1 , were reduced [ 37 , 38 , 39 , 40 , 41 ]. The increase in these oxygen-containing functional groups revealed the due to oxygen atom bonding to hydrogen atoms on the surface during O 2 plasma treatment [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…A plasma surface treatment system is a unique modification technology that is an advantageous and versatile technique in which plasma activation treatment and surface graft polymerization achieve uniformity and function [ 35 , 36 , 37 , 38 ]. Plasma treatment is used to alter the surface properties to increase the adhesion, wettability, and other surface characteristics of various materials [ 37 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing demand for high-quality textile materials, especially in the automobile and leisure industries, has driven the development of high-value-added synthetic fibers in which the advantages of synthetic and natural fibers are supplemented [1][2][3][4]. For example, the consumption of modified polyethylene terephthalate (PET) fibers, which are economical and exhibit excellent mechanical properties and chemical stability, has grown substantially in recent years [4][5][6][7][8][9]. To address the problem of uniformly textured PET fibers, the development of properties such as soft texture, flexibility, glossy drape, and absorptivity similar to those of nylon and rayon has been an engaging subject of study [10].…”
Section: Introductionmentioning
confidence: 99%
“…In order to enhance other applications of the materials, and without there being any deterioration in the bulk properties, surface modification plays a very important role in various fields [8,9,10,11,12,13]. There are several methods that have been considered and developed for altering the interactions of materials with their environments, such as adsorption, oxidation by strong acids, ozone treatment, plasma (glow discharge), corona discharge, photo activation (UV), ion, electron beam, and so on [14,15,16,17]. Among these methods, plasma surface modification processes account for most of the commercial uses of plasma technology because they are fast, efficient methods for increasing the adhesion, wettability properties and other surface characteristics of a variety of materials [7,18,19,20].…”
Section: Introductionmentioning
confidence: 99%